The Difference of Irrigant Solution between Red Pine Extract (Pinus densiflora) and Green Pine Extract (Pinus merkusii) Against Cleanliness of Root Canal Walls - Dian Agustin Wahjuningrum; Setyabudi Setyabudi; Sukaton Sukaton; Yuline Krishartini (Conservative Dentistry Journal, 2020)
Background: Smear layer is an accumulation of organic material, debris, and inorganic material in root canal wall. Irrigant solution must be able to eliminate organic and inorganic materials. Herbal extract such as pine contain saponins that can dissolve organic and inorganic materials. Korea is a country that has used pine in this case red pine as an antibacterial medicament. In Indonesia, there are also green pine species. Purpose: To explain the differences in cleanliness of the root canals after irrigation using extracts of red pine (Pinus densiflora) and green pine (Pinus merkusii). Methods: This study used twenty-seven mandibular premolar teeth which were divided into 3 groups each group consisted of 9 premolar teeth. All samples were prepared using ProTaper for Hand Use and irrigated. Group I was irrigated using 2.5% NaOCl, group II was irrigated with red pine extract, and group III was irrigated using green pine extract. Tooth that has been prepared, were cut vertically into 2 and cut horizontally in 1/3 apical section. The root canal surface was observed using a scanning electron microscope. Photomicrograph was observed by three observers using a score and performed an analysis test. Results: There were no difference between red pine (Pinus densiflora) and green pine (Pinus merkusii) in root canal cleanliness with a significance value of 0.169 (p> 0.05) Conclusion: Red pine extract had the same smear layer cleaning power as green pine extract.